Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1518784
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing real-time language-based feedback on teamwork behavior in computer-mediated groups

Abstract: While most collaboration technologies are concerned with supporting particular tasks such as workflows or meetings, many work groups do not have the teamwork skills essential to effective collaboration. One way to improve teamwork is to provide dynamic feedback generated by automated analyses of behavior, such as language use. Such feedback can lead members to reflect on and subsequently improve their collaborative behavior, but might also distract from the task at hand. We have experimented with GroupMeter -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 39 publications
(51 reference statements)
1
53
1
Order By: Relevance
“…As explained in [24], feedback can take on many different forms and uses. Thus, it is important to look at the literature on feedback to determine which characteristics are most important when developing a display that is intended to increase team interactions.…”
Section: Related Feedback Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…As explained in [24], feedback can take on many different forms and uses. Thus, it is important to look at the literature on feedback to determine which characteristics are most important when developing a display that is intended to increase team interactions.…”
Section: Related Feedback Literaturementioning
confidence: 99%
“…Large amounts of feedback information can often be confusing, because it may seem irrelevant to a specific task or event. According to researchers, it is especially important that automatically-generated feedback systems provide clear explanations about how the display information is calculated, and how it changes over time [24].…”
Section: Characteristics Of Effective Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dashboards have historically been more limited to providing feedback on specific, shorter-duration interactions, even when used among longer term project teams (e.g., [10,18,31]). …”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Leshed et al demonstrated that visual feedback based on language can encourage more positive language in text-based chat environments [27]. The public awareness and resulting accountability for negative comments discouraged overly negative criticism.…”
Section: Visual Signalsmentioning
confidence: 99%